Efficacy of Iron-Rich Premix Mineral Supplementation on Egg Yolk's Fe Content and Egg Quality - Hanim, Chusnul; Hanif, Muhammad Fathin; Agus, Ali (Faculty of Animal Science, Universitas Gadjah Mada, 2024)
Iron's significance in human health and diseases has been extensively examined in recent reviews, leading to the consensus that iron insufficiency is a worldwide issue requiring immediate attention. Fe-enriched eggs are significant for delivering this essential trace mineral to humans. This study aimed to assess the effects of adding premix minerals on the physical and chemical quality of eggs and the yolk's iron levels. 1,680 Lohman brown laying hens, aged 31 weeks (body weight: 1.70±0.11 kg, egg production average: 81.2 %), were divided into two groups (n = 840) and fed different diets for six weeks. The diets included a basal diet (CON) and a diet enriched with a 2.5 g / kg food premix mineral (PM-Fe). The findings indicated that there was no impact on the physical and chemical quality of the eggs. However, compared to the control diet, the addition of premix significantly enhanced the iron level in the yolk after 42 days (p<0.05). To summarize, adding 2.5 g per kg of premix mineral (which contains 12.6 g per kg of iron premix) can result in a 23.4% rise in iron content in the diet and a 15.7% increase in iron content in the egg yolk.